2017
DOI: 10.9734/air/2017/33424
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid and Functional Characteristics of Pawpaw (Carica papaya) Seeds under Normal Storage Ripening

Abstract: The amino acid contents and the functional properties of matured unripe, ripe and overripe pawpaw (Carica papaya) seeds were carried out using standard methods as follow up to a previous paper where some aspects of the chemical composition of the seeds at different ripening stages were determined. Twenty amino acids comprising ten essential and non-essential amino acids were detected, out of which total essential amino acids (EAA) in % were 48, 47 and 24 while nonessential amino acids in % were 52, 53 and 76 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Oyeleke et al . [ 21 ] formerly noticed that amino acids, particularly lysine and methionine, were higher in the papaya seed from the ripe than those in the mature unripe papaya. However, the levels of lysine and methionine decreased in the seed of overripe papaya when compared with those in ripe papaya seed [ 21 ].…”
Section: Papaya Seed As Protein Source For Poultrymentioning
confidence: 99%
See 1 more Smart Citation
“…Oyeleke et al . [ 21 ] formerly noticed that amino acids, particularly lysine and methionine, were higher in the papaya seed from the ripe than those in the mature unripe papaya. However, the levels of lysine and methionine decreased in the seed of overripe papaya when compared with those in ripe papaya seed [ 21 ].…”
Section: Papaya Seed As Protein Source For Poultrymentioning
confidence: 99%
“…[ 21 ] formerly noticed that amino acids, particularly lysine and methionine, were higher in the papaya seed from the ripe than those in the mature unripe papaya. However, the levels of lysine and methionine decreased in the seed of overripe papaya when compared with those in ripe papaya seed [ 21 ]. The latter authors further suggested that microbial activities taking place during the process of ripening seem to be responsible for the lower amino acids in the seed from the overripe papaya.…”
Section: Papaya Seed As Protein Source For Poultrymentioning
confidence: 99%